(untitled) (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2021)
The anxiety of pregnant women has increased during the pandemic, especially when participating in the Covid-19 Screening in the third trimester as a condition for childbirth. So this study aims to determine the relationship between the results of Covid-19 screening in pregnant women and the level of anxiety of pregnant women at the Tambakboyo Health Center in 2021. The type of research used was analytic with a cross-sectional design. The population was all pregnant women in the third trimester as many as 85 people. The sample size was 70 people using the Simple Random Sampling technique. The independent variable was the results of the Covid-19 Screening in pregnant women and the dependent variable is the level of anxiety of pregnant women. This study used secondary data, namely the results of the Rapid test and primary data using an interview guide. The results of the study showed that the majority (62.9%) of Covid-19 screening results were non-reactive pregnant women. Almost all (77.1%) pregnant women experienced moderate levels of anxiety and almost all (79.5%) pregnant women with moderate levels of anxiety obtained the results of the rapid test, which was non-reactive. The results of the Chi-Square test obtained a p-value = 0.533, so there was no significant relationship between the results of the Covid-19 Screening in pregnant women and the level of anxiety of pregnant women. It is hoped that further researchers will research other factors that affect the level of anxiety of pregnant women during the pandemic.